Asymmetric synthesis of spiro-structural 2, 3-dihydrobenzofurans via the bifunctional phosphonium salt-promoted [4 + 1] cyclization of ortho-quinone methides with α-bromoketones. Issue 22 (18th October 2019) - Zhang, Song; Yu, Xiaojun; Pan, Jianke; Jiang, Chunhui; Zhang, Hongsu; Wang, Tianli
Abstract : A practical and scalable method for highly stereoselective construction of spiro-2, 3-dihydrobenzofurans via cyclization of ortho -quinone methides and α-bromoketones by bifunctional phosphonium salt catalysis was developed. Abstract : We report a practical and scalable method for the highly diastereo- and enantio-selective construction of 2, 3-dihydrobenzofurans bearing spiro-structures by means of cyclization reactions between ortho -quinone methides and α-bromoketones through bifunctional phosphonium salt catalysis under mild conditions. A variety of spiro-fused 2, 3-dihydrobenzofuran derivatives were readily synthesized in high yields with excellent diastereo- and enantio-selectivities (up to >20 : 1 dr and 97% ee). This protocol represents an alternative facile way for preparing biologically important chiral 2, 3-dihydrobenzofurans. Moreover, mechanistic observations indicated that the hydrogen bonding interaction between the Brønsted acid moiety of the phosphonium catalyst and the "CO" unit of the quinone is crucial for stereoinduction.